arc/sec: Reactive architecture. St Paul St Gallery, AUT University, 12 September – 4 October 2008 - Douglas, C (Auckland, NZ: Enigma, 2008)
[arc/sec], a recent exhibition of environmentally-responsive architectural systems at AUT’s St. Paul St Gallery, is premised on the value of interconnectedness instead of isolation. As Goethe recognized, few things make sense in isolation. In his morphological studies, he concluded that natural form could only be understood in the context of the forces which have given it shape. To understand something, we need to understand how it engages with everything else. Aligning with this view, each of the projects in [arc/sec] is conceived as a response to contextual forces: social, cultural and especially natural. They are understood in terms of formation rather than form, morphogenesis rather than morphology.
Keywords: exhibition; architecture; sustainability; responsive systems